Analisis Kadar Gula Total dan Kekerasan pada Produk Crackers Substitusi Tepung Daun Kelor (Moringa Oleifera) - Inasan Lulu Milatina; Sudrajah Warajati Kisnawaty; Aan Sofyan (Yayasan Literasi Sains Indonesia, 2026)
Introduction: Moringa oleifera leaves are one of the local plants that contain high nutrition and have the potential to be used as a fortification ingredient for food products. The purpose of this study was to analyze the effect of moringa leaf flour substitution on the total sugar content and hardness of crackers as an effort to develop food based on local ingredients. Method: The experimental method was applied in this study with a Completely Randomized Design (CRD) containing four treatments of moringa leaf flour substitution. Testing of total sugar content and hardness used the Nelson-Somogyi method and Texture Analyzer. Data analysis used the Kruskal Wallis test. Results: The findings showed that moringa leaf flour substitution significantly affected the total sugar content and hardness of crackers (p≤0.05). The total sugar content increased with increasing substitution from 17.23% in 0% treatment to 18.73% in 20% substitution, while the hardness value increased at 10% substitution (15.09 N) then decreased at 15% substitution (12.92 N) and 20% (10.01 N). These findings indicate that changes in flour composition affect the chemical and physical properties of the product and there is an influence between total sugar content and hardness in determining the physical quality of crackers. Conclusion: The addition of moringa leaf flour has been proven to affect the characteristics of crackers so that the material formulation needs to be optimized to produce products with good quality.